Analisis kandungan minyak pada saat pasang dan Surut di perairan sekitar pelabuhan Gunungsitoli kabupaten nias - Damai S Harefa; Syahril Nedi; Bintal Amin (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This study was carried out in February 2014, with the aim to analyze the oilcontent during high and low tide in the different area in coastal waters aroundGunungsitoli Port of Nias Regency. This study was expected to serve as the initialinformation about the content and distribution of oil in the water and can be used as areference in reviewing the environmental conditions in the waters of GunungsitoliPort of Nias Regency. The results showed that the average oil content was 0.256 ppmat high tide and 0.193 ppm at low tide. The average oil content was not significant bydefferent (p > 0.05) betweel high and low tide. The oil content during high tide basedon the distance from the beach were as follow : 0.281 ppm near the beach, 0.273 ppmin te middle and 0.214 ppm in auter coastal. Meanwhile during the low tide the oilcontent were 0.0234 ppm at the beach, 0.174 ppm in the middle, and 0.172 ppm inthe auter coastal, respectively. Based on the distance from shore oil content showedno significant difference (p > 0.05). Oil content in the port / area was 0.288 ppm, intourist areas / settlement, 0.237 ppm, and in the Depo Pertamina was 0.244 ppm andthey showed no significant diffrence (p > 0.05).Keywords: Oil Content, Tidal, Gunungsitoli Port.